2020
DOI: 10.4171/205-1/7
|View full text |Cite
|
Sign up to set email alerts
|

A study on prefixes of $c_2$ invariants

Abstract: This paper begins by reviewing recent progress that has been made by taking a combinatorial perspective on the c 2 invariant, an arithmetic graph invariant with connections to Feynman integrals. Then it proceeds to report on some recent calculations of c 2 invariants for two families of circulant graphs at small primes. These calculations support the idea that all possible finite sequences appear as initial segments of c 2 invariants, in contrast to their apparent sparsity on small graphs.Thanks to Oliver Schn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In our results, we show that the ratio of unique c 2 invariants to prime ancestors does not change much between different loop orders. A related observation about the distribution of c 2 invariants appeared in [37]. One of us in [37] showed that the distribution of decompleted c 2 prefixes for the circulant graphs C n .1; 3/ and C n .2; 3/ is very uniform as we increase n. This uniformity, even within the same family of graphs, gave rise to the idea that maybe all finite prefixes show up in 4 c 2 invariants if the loop order is high enough.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In our results, we show that the ratio of unique c 2 invariants to prime ancestors does not change much between different loop orders. A related observation about the distribution of c 2 invariants appeared in [37]. One of us in [37] showed that the distribution of decompleted c 2 prefixes for the circulant graphs C n .1; 3/ and C n .2; 3/ is very uniform as we increase n. This uniformity, even within the same family of graphs, gave rise to the idea that maybe all finite prefixes show up in 4 c 2 invariants if the loop order is high enough.…”
Section: Discussionmentioning
confidence: 77%
“…A related observation about the distribution of c 2 invariants appeared in [37]. One of us in [37] showed that the distribution of decompleted c 2 prefixes for the circulant graphs C n .1; 3/ and C n .2; 3/ is very uniform as we increase n. This uniformity, even within the same family of graphs, gave rise to the idea that maybe all finite prefixes show up in 4 c 2 invariants if the loop order is high enough. This line of thought seems to be supported by the evidence of the present calculations.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The c 2 has been studied quite deeply in the context of ฯ• 4 quantum field theory (Section 2.7). The focus of these studies can either be the general mathematical structure of the c 2 [11,15,31] or the zoology of the geometries identified by c 2 s [9,10,13,27,30,32]. The nature of this article is more in the latter direction, particularly when we analyze the c 2 s of small kernels in Section 4.…”
Section: The C 2 Invariantmentioning
confidence: 99%
“…In a certain sense these hourglass chains can be considered as 'telescopes' that enable us to look into geometries of Feynman graphs at very high loop order (i.e., the number of independent cycles in L โˆ’ v). This has never been achieved before: all previous techniques were either restricted to the analysis of small graphs, or they worked in a way which was fundamentally prime-by-prime [13,30,32] and hence did not lead to non-trivial graph families with the same underlying geometries.…”
Section: Introductionmentioning
confidence: 99%